Mobilisasi Dini dan Penurunan Skala Nyeri pada Pasien Post Operasi TURP Benign Prostate Hyperplasia - I Wayan Sumberjaya; I Made Mertha (Jurnal Gema Keperawatan, 2020)
Pain is an unpleasant symptom experienced by patients who undergoing post surgery of TURP BPH. One technique used to reduce pain after surgery is early mobilization techniques. This study aimed to determine the effect of early mobilization on reducing pain scale in post surgery patients with TURP BPH. The design of this study was one group pre-post test design with a pre-experimental design, with a total sample was 12 respondents using purposive sampling technique. The instrument used in this study was guide sheet in the form of Standard Operating Procedures (SOP) and a pain gauge in the form of Numeric Rating Scale (NRS). Pain scale before early mobilization, 2 respondents (16.7%) were with pain scale 6 and 3 respondents (25%) were with pain scale 3. After early mobilization, 1 respondent (8.3%) was with pain scale 5 and 3 respondents ( 25%) were with pain scale 2. Wilcoxon test results obtained p-value = 0.0001 0.05, it means that the provision of early mobilization had a significant effect on pain scale reduction in post surgery patients with TURP Benign Prostate Hyperplasia (BPH) in Bima Ward Sanjiwani Regional Hospital Gianyar. The results of the study concluded that there was effect on pain scale reduction in post surgery patients with TURP BPH. The results of the study are expected to be used as a reference in enhancing the development of independent interventions on acute pain nursing problems.